A management of neutropenia using granulocyte colony stimulating factor support for chemotherapy consisted of docetaxel, cisplatin and 5-fluorouracil in patients with oesophageal squamous cell carcinoma. (5th November 2020) - Katada, Chikatoshi; Sugawara, Mitsuhiro; Hara, Hiroki; Fujii, Hirofumi; Nakajima, Takako Eguchi; Ando, Takayuki; Kojima, Takashi; Watanabe, Akinori; Sakamoto, Yasutoshi; Ishikawa, Hideki; Hosokawa, Ayumu; Hamamoto, Yasuo; et al.
Abstract: Background: An exploratory study was designed to evaluate the efficacy of granulocyte colony stimulating factor support for chemotherapy consisting of docetaxel, cisplatin and 5-fluorouracil chemotherapy in patients with oesophageal cancer. Methods: The inclusion criteria were as follows: (1) oesophageal squamous cell carcinoma, (2) a schedule to receive three courses of induction chemotherapy (docetaxel 75 mg/m 2 day 1, cisplatin 75 mg/m 2 day 1, 5-fluorouracil 750 mg/m 2 days 1–5, every 3 weeks), (3) stage IB-III, (4) 20–75 years old, (5) 0–1 performance status, (6) preserved organ functions and (7) written informed consent. The endpoints were to evaluate the efficacy of granulocyte colony stimulating factor support including secondary prophylactic usage for docetaxel, cisplatin and 5-fluorouracil chemotherapy. Patients who previously had 'febrile neutropenia', or 'Grade 3 or 4 infection accompanied by grade 3 or 4 neutropenia' prophylactically received granulocyte colony stimulating factor support from day 7. Results: A total of 91 patients were included in the analysis. Granulocyte colony stimulating factor support was given to 81.3%. The incidence of grade 4 neutropenia and febrile neutropenia were 81.3 and 32.9%, respectively. The dose of anticancer agents was reduced in 48.4%. There were no treatment-related deaths. The relative dose intensity of docetaxel, cisplatin and 5-fluorouracil were 92.7 ± 9.8%, 86.0 ± 15.6% and 91.8 ± 10.0%, respectively. In the secondary prophylactic granulocyte colony stimulating factor support group, the neutrophil count significantly increased between day 7 and day 13 as compared with the non-prophylactic granulocyte colony stimulating factor support group ( P < 0.05 for each day). Conclusions: Granulocyte colony stimulating factor support including secondary prophylactic usage may be feasible for maintaining the intensity of docetaxel, cisplatin and 5-fluorouracil chemotherapy in patients with oesophageal cancer. Abstract : Granulocyte colony stimulating factor support including secondary prophylactic usage may be feasible for maintaining the intensity of chemotherapy consisting of docetaxel, cisplatin and 5-fluorouracil in patients with oesophageal cancer.